Generation and Maintenance of ILIAD™ Medical Knowledge in a HyperCard™ Environment - Sorenson, Dean (1988)
A comprehensive system has been constructed to systematically and efficiently 1) design, translate, compile, and test new knowledge frames, and 2) update and facilitate access to text frames, associated literature citations, and statistical information. The availability of the knowledge building tools in a unified workstation environment has synergistically accelerated the process of building, updating, and maintaining medical knowledge bases.